Identification and diagnosis of autism spectrum disorders: an update. Issue 1 (February 2010) - Pasco, Greg
Over the past two decades knowledge of and interest in autism has increased dramatically amongst both medical professionals and the wider public, and the relatively heterogeneous nature of the autism spectrum has become widely accepted. The expansion of the concept of the autism spectrum and the consequent rise in the number of people diagnosed with autism has led to controversy as to whether the true incidence of autism is on the increase or whether better diagnostic practice means that previously unidentified cases are no longer missed. Whereas autism is predominantly understood in dimensional terms today, the most authoritative definitions of autism and the diagnostic instruments used clinically and in research are still linked to a more categorical framework. Recently, there has been much interest in the early identification and diagnosis of autism, although the utility of universal early screening for autism spectrum disorders has not yet been demonstrated.